Anthropometric measurements, dietary intake and plasma lipoproteins in throwing field athletes - Faber, Willemina Maria (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Nutrition)) -- University of Stellenbosch, 1992.